Hubungan Pengetahuan Kesehatan Reproduksi dengan Perilaku Seksual Remaja di SMA Negeri 8 Padangsidimpuan - Lena Juliana Harahap; Lia Junita Harahap (Bioedunis Journal, 2022)
Reproductive health is complete physical, mental and social well-being not only because it is free from disease or disability, in all aspects related to the reproductive system, its functions and processes which include men or women. The research was conducted with the aim of knowing the relationship between reproductive health knowledge and sexual behavior in Class X SMA Negeri 8 Padangsidimpuan. This research is an analytic research with cross sectionalapproach. The sampling technique is simple random sampling of 33 students and analyzed by Chi-square test. The results of this study show that there is a relationship between reproductive health knowledge and sexual behavior with p = 0.005 ≤ 0.05. So it can be concluded that there is a relationship between knowledge of reproductive health and sexual behavior, it is suggested to health workers to provide counseling to adolescents regarding reproductive health more often to avoid unhealthy sexual behavior